Power Efficient LNA for Satellite Communications - Al-Anbagi, Haidar N.; Abdulhameed, Abdulghafor A.; Jasim, Ahmed M.; Jahanbakhshi, Maryam; Obaid, Abdulhameed Al (Iraqi Journal for Electrical and Electronic Engineering, 2023)
This article presents a power-efficient low noise amplifier (LNA) with high gain and low noise figure (NF) dedicated to satellite communications at a frequency of 435 MHz. LNAs’ gain and NF play a significant role in the designs for satellite ground terminals seeking high amplification and maintaining a high signal-to-noise ratio (SNR). The proposed design utilized the transistor (BFP840ESD) to achieve a low NF of 0.459 dB and a high-power gain of 26.149 dB. The study carries out the LNA design procedure, from biasing the transistor, testing its stability at the operation frequency, and finally terminating the appropriate matching networks. In addition to the achieved high gain and low NF, the proposed LNA consumes as low power as only 2 mW.